2015
DOI: 10.1128/aac.00354-15
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Second-Line Antituberculosis Drugs after Multiple Administrations in Healthy Volunteers

Abstract: dTherapeutic drug monitoring (TDM) of second-line antituberculosis drugs would allow for optimal individualized dosage adjustments and improve drug safety and therapeutic outcomes. To evaluate the pharmacokinetic (PK) characteristics of clinically relevant, multidrug treatment regimens and to improve the feasibility of TDM, we conducted an open-label, multiple-dosing study with 16 healthy subjects who were divided into two groups. Cycloserine (250 mg), p-aminosalicylic acid (PAS) (5.28 g), and prothionamide (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 13 publications
0
20
1
Order By: Relevance
“…We found that the C max and AUC of KM were in accordance with the expected range. 19 , 23 A higher C max was found in a small study of patients treated for MDR-TB in Korea with a higher dose of KM. 24 Lidocaine had no effect on KM pharmacokinetics; this finding is in line with the findings of others who have assessed the effect of lidocaine on the pharmacokinetics of other drugs when administered intra-muscularly.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We found that the C max and AUC of KM were in accordance with the expected range. 19 , 23 A higher C max was found in a small study of patients treated for MDR-TB in Korea with a higher dose of KM. 24 Lidocaine had no effect on KM pharmacokinetics; this finding is in line with the findings of others who have assessed the effect of lidocaine on the pharmacokinetics of other drugs when administered intra-muscularly.…”
Section: Discussionmentioning
confidence: 90%
“…Using the report by Park et al describing KM pharmacokinetics, 19 and assuming that data would be non-parametric, we estimated that a minimum of 16 patients would be required to detect a 20% change in pharmacokinetics between the two groups. Considering the paucity of data on KM pharmacokinetics, we considered a target sample size of 20 participants would be sufficient to allow for any inaccuracy in power estimation.…”
Section: Study Population and Methodsmentioning
confidence: 99%
“…However, limited data are available on its PK/PD in TB patients. Several studies have reported the plasma concentrations of cycloserine, but many of them included 1 to 2 concentrations in therapeutic drug monitoring settings (5, 1419). Although the typical C max for cycloserine is usually thought to be between 20 to 35 mg/liter after a 250 or 500 mg dose in adults (20), a few studies have reported lower plasma concentrations in some MDR-TB patients using the same doses (16, 17).…”
Section: Discussionmentioning
confidence: 99%
“…Streptomycin was the first discovered aminoglycoside antibiotic in 1943 and became the first effective treatment for tuberculosis in 1946 (Mitchison, ). It is still a first‐line antibiotic for Gram‐negative bacteria infection in veterinary practice (Schatz, Bugie, & Waksman, ) and is also used as a second‐line antituberculosis drug for patients with resistance to isoniazid and rifampin (Park et al, ). Streptomycin has also been widely applied in veterinary medicine for the prevention and treatment of bacterial infection.…”
Section: Introductionmentioning
confidence: 99%